ll Noite cultural - Silvério, Agda Rodrigues Rios; Oliveira, Vera lúcia Gonçalves de; Lima, Eliene Xavier de; Oliveira, Maria Auxiliadora de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf